Tecumseh, Lenawee Co., Michigan 1868. - Ruger, A.; Chicago Lithographing Co.; Glover, E. S. (Eli Sheldon), 1844-1920. (1868)
AACR2: 100; 651/1; 700/1; 710/2; LC Panoramic maps (2nd ed.), 378; Includes ill. and index to points of interest.; Bird's-eye view.; Vault; Available also through the Library of Congress Web site as a raster image.; Perspective map not drawn to scale.